A tale of two cities: a comparison between the Detroit and Johannesburg urban experience - Stainer, Duncan Charles (My University, 2014)
The two cities, Johannesburg and Detroit, having experienced decentralization together with ubiquitous inner city blight, form the topic of this discourse. The historical backgrounds of both cities are important in that both developed as nineteenth century industrial towns and the origins of decentralization can be traced to the reaction against the overcrowding and environmental pollution which accompanied the Industrial Revolution. Then again, both cities have experienced problems of a racial nature. The causes of decentralization in both cities are analysed and found to be remarkably similar. Both Johannesburg and Detroit, as car-based cities developed multiple suburban nodes. Firstly, the preferred model for living became the suburban house on its own plot of ground. Secondly, businesses moved into low-rise offices in landscaped garden settings, convenient to where people lived. Thirdly, the preferred form of shopping became the shopping mall with ample parking and safe inner pedestrian walkways. The exodus o f middle class residents, together with businesses, resulted in both inner cities becoming poorer, more crime ridden and increasingly populated by disadvantaged black people. These urban realities are not unique to Johannesburg and Detroit, but are modem trends wh; zh have affected many cities around the world. The conclusion discusses the current literature on decentralization and the debate central to urban planning, that between decentralization on the one hand and on the other hand, concentration and the compact city. Solutions to Johannesburg’s increasingly impoverished inner city are offered. Considering the similarities between the Johannesburg and Detroit urban experience, it would be an easy option to seek for similar solutions. However, although Johannesburg’s economic decline may be compared to Detroit’s, it is important to realize that American solutions may not be rek t to the Johannesburg situation. In most American cities, including Detroit, residents outside the original city’s boundaries established separate local governments. Unable to tap the area of greater economic growth, (its suburbs) Detroit became increasingly poorer. Many American urban experts such as David Rusk argue that the surest way to reverse patterns of economic decline is to create metropolitan governments. The restructuring of the Greater Johannesburg Metropolitan Council and its four substructures :nio a single megacity will result in such a metropolitan government and will allow for more monev in be allocated to the inner city. Or a cautionary note, the megacity may not necessarily resyB v‘ more efficient government. Unlike Detroit, Johannesburg’s inner city has seen a substantial increase in its residential population. Thus the greatest urban challenge facing Johannesburg lies in its ability to accommodate its rapidly expanding black population. It is vitally important that the inner city develop a framewc; V of social housing to supplement the national housing shortage. Office buildings standing empty in the CBD may be converted to residential use. Then again, tenants of blocks of flats may pool their individual government housing subsidies and buy the buildings which they would then all jointly own. In many cases this is already happening. But if Johannesburg’s inner city is not to be become a urban ghetto, middle class black families will have to be encouraged to reside in the city. The two preconditions for attracting middle class residents to the inner city are firstly, to provide a quality education for their children and secondly, to provide a safer and more attractive env'mnment. Obviously adequate city management, encompassing clean streets, better policing and greater control of informal traders is important. A more attractive environment would also ensure that the CBD remains a major retail centre for the African market. However, the successful renewal o f the inner city depends on an economic upliftment programme rather than on a better city management programme. It may be necessary to accept that while it is extremely unlikely that the more affluent suburbanites will repopulate the inner city, it is equally unlikely that leading businesses will move back into the CBD. But the compactness of the Johannesburg city centre with its plentiful supply of cheap office space and empty warehouses is ideally suited to promoting small and medium black businesses. Ultimately, the revitalization of the inner city depends on improving the economic positi on of the residents. It is important that there is sound city leadership and co-operation between the private sector, metropolitan government and local communities. Unfortunately, in contrast to America, South Africa is unlikely to have surplus public funds available to subsidize significant urban development. However, with insight and realistic goals, Johannesburg’s inner city may become once again a vibrant and dynamic centre.